Reliability of data on caesarean sections in developing countries - Cynthia K. Stanton; Dominique Dubourg; Vincent De Brouwere; Mar Pujades; Carine Ronsmans (The World Health Organization, 2005)
OBJECTIVE: To examine the reliability of reported rates of caesarean sections from developing countries and make recommendations on how data collection for surveys and health facility-based studies could be improved. METHODS: Population-based rates for caesarean section obtained from two sources: Demographic and Health Surveys (DHS) and health facility-based records of caesarean sections from the Unmet Obstetric Need Network, together with estimates of the number of live births, were compared for six developing countries. Sensitivity analyses were conducted using several different definitions of the caesarean section rate, and the rates obtained from the two data sources were compared. FINDINGS: The DHS rates for caesarean section were consistently higher than the facility-based rates. However, in three quarters of the cases, the facility-based rates for caesarean sections fell within the 95% confidence intervals for the DHS estimate. CONCLUSION: The importance of the differences between these two series of rates depends on the analyst's perspective. For national and global monitoring, DHS data on caesarean sections would suffice, although the imprecision of the rates would make the monitoring of trends difficult. However, the imprecision of DHS data on caesarean sections precludes their use for the purposes of programme evaluation at the regional level.